The role of microfinance institutions on women's entrepreneurship development - Abraham Abebe; Meketaw Kegne (Journal of Innovation and Entrepreneurship, 2023)
This study investigates the role of microfinance services on women's entrepreneurship development in Assosa town. The study employed both descriptive and explanatory designs and a quantitative research approach. The study targeted 352 women clients of Assosa Woreda Microfinance Institution, and 165 samples were selected using a simple random sampling technique. The data were collected through a questionnaire and analyzed through the statistical package for social science (SPSS) 26 software. The findings from the descriptive mean analysis indicate that the microfinance institution financial and non-financial services offered were found unable to significantly empower disadvantaged and poor women by improving their livelihood and development of their business. The correlation result also indicated a positive and significant association between saving practice, access to credit, skill development training, and the development of women entrepreneurs. Finally, the regression result saving and the credit or loan services of the microfinance institution service have the most decisive influence on women's entrepreneurship development.
Keywords: 650; Access to finance; Business support; Microfinance institution; Saving; Skill development; Women entrepreneurship